2019
DOI: 10.1007/s00167-019-05751-5
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps tendon autograft for anterior cruciate ligament reconstruction is associated with high revision rates: results from the Danish Knee Ligament Registry

Abstract: Purpose The quadriceps tendon (QT) has recently gained interest as an anterior cruciate ligament reconstruction (ACLR) autograft. There is a paucity of data from large cohort studies on failures and revision rates after ACLR using the QT graft. The purpose of the present study is to use the Danish Knee Ligament Reconstruction Registry (DKRR) to compare revision rates, objective knee stability and subjective clinical outcomes in patients who have undergone ACLR with QT, hamstring tendon (HT), and patellar tendo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 32 publications
1
56
3
Order By: Relevance
“…A large registry study that compared QT/QTB, HT, and patellar tendon (PT) grafts in ACLR 25 showed a 4.7% revision rate for QT, which was higher than that in our study, and a 2.3% rate for HT, similar to that found in our study. The investigators compared the rates of revision ACLR at 2 years after surgery in patients registered in the DKRR: 581 patients with QT, 14,312 patients with HT, and 1835 patients with PT.…”
Section: Graft Failure and Revision Aclrsupporting
confidence: 85%
See 2 more Smart Citations
“…A large registry study that compared QT/QTB, HT, and patellar tendon (PT) grafts in ACLR 25 showed a 4.7% revision rate for QT, which was higher than that in our study, and a 2.3% rate for HT, similar to that found in our study. The investigators compared the rates of revision ACLR at 2 years after surgery in patients registered in the DKRR: 581 patients with QT, 14,312 patients with HT, and 1835 patients with PT.…”
Section: Graft Failure and Revision Aclrsupporting
confidence: 85%
“…38 It has been argued that the in vitro biomechanical and anatomic features of the QT can be disadvantageous because the lack of parallel fibers might lead to graft elongation over time. 25 Slone et al 38 reported that despite variability in morphologic characteristics of the QT, its use is safe, versatile, and reproducible, with consistent length, depth, and width. Our results are in line with this.…”
Section: Graft Failure and Revision Aclrmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, a recently published Danish registry study, including high-and low-volume orthopaedic departments, found a higher rerupture rate for the QT autograft (4.7%) as compared with the HT autograft (2.3%), whereas the QT revision rate dropped to 1.6% when only highvolume departments were included. 22,23 Lind et al 21 reported in a prospective randomized study no significant difference in rerupture rate between 50 patients treated with QT autografts and 49 patients treated with HT autografts. In the present study, graft choice was a factor significantly influencing the risk of graft rupture, with the odds of rerupture being 2.7 times greater in patients with an HT autograft (4.9%) than a QT autograft (2.8%; Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, the failure rate in high-risk patients is still to be assessed through registry data and or RCTs to state the superiority of the QT graft. The Danish Registry43 reported a greater failure rate with QT grafts. They showed a 4.9% failure rate for QT, a 2.7% failure rate for HT and a 1.6% failure rate for BPTB.…”
Section: Donor Site Morbiditymentioning
confidence: 99%